2011
DOI: 10.1523/jneurosci.2672-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

A Signaling Cascade of Nuclear Calcium-CREB-ATF3 Activated by Synaptic NMDA Receptors Defines a Gene Repression Module That Protects against Extrasynaptic NMDA Receptor-Induced Neuronal Cell Death and Ischemic Brain Damage

Abstract: Synapse-to-nucleus signaling triggered by synaptic NMDA receptors can lead to the buildup of a neuroprotective shield. Nuclear calcium activating the cAMP response element binding protein (CREB) plays a key role in neuroprotection acquired by synaptic activity. Here we show that in mouse hippocampal neurons, the transcription factor Atf3 (activating transcription factor 3) is a direct target of CREB. Induction of ATF3 expression by CREB in hippocampal neurons was initiated by calcium entry through synaptic NMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 65 publications
4
118
0
3
Order By: Relevance
“…Although CREB is mostly known as an activator, it has been found to inhibit transcription, and whether it acts as a repressor depends on its phosphorylation status (41), the partners recruited in transcriptional complexes (42), and the regulatory region of the gene to which CREB binds (43). Alternatively, CREB negative effect on gli1 transcription may be indirect by inducing expression of a repressor (44).…”
Section: Discussionmentioning
confidence: 99%
“…Although CREB is mostly known as an activator, it has been found to inhibit transcription, and whether it acts as a repressor depends on its phosphorylation status (41), the partners recruited in transcriptional complexes (42), and the regulatory region of the gene to which CREB binds (43). Alternatively, CREB negative effect on gli1 transcription may be indirect by inducing expression of a repressor (44).…”
Section: Discussionmentioning
confidence: 99%
“…In wild-type neurons, overexcitability due to excessive NMDA-receptor signaling activates the calcium-CREB pathway to eventually enhance the expression of Atf3 (Hashimoto et al, 2002;Zhang et al, 2009Zhang et al, , 2011. Atf3 expression is also induced in sensory and motor neuron following axotomy (Tsujino et al, 2000;Seijffers et al, 2007).…”
Section: Atf3 Is Highly Upregulated In Neuronal Tsc Modelsmentioning
confidence: 99%
“…Our previous study has demonstrated an mTOR-dependent induction of Hmox1 (heme oxygenase-1) in Tsc2-deficient neurons, indicating an enhanced oxidative stress response (Di Nardo et al, 2009). Atf3 is a transcription factor in the CREB protein family that is induced by action potential bursting and nuclear calcium signaling Zhang et al, 2011;Hunt et al, 2012). Hmox1 also has anti-inflammatory effects.…”
Section: Stress-responsive and Antiinflammatory Proteins In Tsc And Amentioning
confidence: 99%
“…ATF3 transcriptional targets vary in different cell types and conditions, resulting in diverse influences on cellular phenomena, such as cell survival, proliferation, and death (15,16). In neurons (17), induction of ATF3 expression prevents cell death and promotes neurite formation and elongation, leading to enhanced nerve regeneration through transcriptional induction of survival and growth-associated genes (18)(19)(20)(21)(22)(23)(24)(25)(26). Intact adult motor neurons do not normally express ATF3.…”
mentioning
confidence: 99%